Caries Risk Profile of Diabetes Mellitus Patients Using Cariogram in Sangkha Hospital, Surin Province - Nimkul K, Thaweedej S, Chusongdej W, Akkapaiboon Okada P (Journal of The Department of Medical Services, 2021)
Background : Diabetes Mellitus (DM) is associated with periodontal disease but the relationship between diabetes mellitus and dental caries is controversy. The cariogram is the one tool of assessment caries risk. Objective : To investigate caries risk profile of diabetes mellitus patients using cariogram in Sangkha Hospital, Surin Province. Method : Data were collected from September to December 2018. The samples comprised 201 patients. Research team collected whole saliva samples, recorded the buffer capacity and salivary rate using questionnaire and oral examination forms in order to calculate risk according to the cariogram model. Caries-related variables were collected and inserted into the cariogram software to calculate the actual chance of avoiding caries. Result : The study showed 75.1% of samples was female, 66.2% was age ≤ 60 yrs. 99.5% was type II diabetes mellitus. The duration of DM was more than 5 years 62.2%. Mean decay, missing and filling of permanent teeth (DMFT) was 8.99 teeth per person. Subjects who had FBS ≤ 130 mg/dl and FBS > 130 mg/dl, mean DMFT was 7.33 teeth per person and 9.66 teeth per person respectively. Those whose age < 60 and ≥ 60, mean DMFT was 8.56 teeth per person and 9.82 teeth per person respectively. Cariogram showed 84.58% of sample had high caries risk (chance to avoid new cavities 61 -100). Conclusion : Diabetes mellitus patients using cariogram in Sangkha Hospital, Surin Province had high caries risk.